Liquidity, innovation, and endogenous growth - Semyon Malamud; Francesca Zucchi (European Central Bank (ECB), 2016)
We study optimal liquidity management, innovation, and production decisions for a continuum of firms facing financing frictions and the threat of creative destruction. We show that financing constraints lead firms to decrease production but may spur investment in innovation (R&D). We characterize which firms should substitute production for innovation in the face of constraints and thus display a "gambling" type of behavior. We embed our firm dynamics into a model of endogenous growth and show that financing frictions have offsetting effects on economic growth.
Keywords: D21; G31; G32; G35; L11; 330; cash management; endogenous growth; financial constraints; innovation